Participation in school and physical education in juvenile idiopathic arthritis in a Nordic long-term cohort study - Ellen Nordal; Veronika Rypdal; Ellen Dalen Arnstad; Kristiina Aalto; Lillemor Berntson; Maria Ekelund; Anders Fasth; Mia Glerup; Troels Herlin; Susan Nielsen; Suvi Peltoniemi; Marek Zak; et al. (BMC, 2019)
Abstract Background The aim of the study was to describe school attendance and participation in physical education in school among children with juvenile idiopathic arthritis (JIA). Methods Consecutive cases of JIA from defined geographical areas of Finland, Sweden and Norway with disease onset in 1997 to 2000 were followed for 8 years in a multi-center cohort study, aimed to be as close to population-based as possible. Clinical characteristics and information on school attendance and participation in physical education (PE) were registered. Results Participation in school and in PE was lowest initially and increased during the disease course. Eight years after disease onset 228/274 (83.2%) of the children reported no school absence due to JIA, while 16.8% reported absence during the last 2 months due to JIA. Full participation in PE was reported by 194/242 (80.2%), partly by 16.9%, and none by 2.9%. Lowest participation in PE was found among children with ERA and the undifferentiated categories. Absence in school and PE was associated with higher disease activity measures at the 8-year visit. School absence > 1 day at baseline predicted use of disease-modifying anti-rheumatic drugs, including biologics (DMARDs) (OR 1.2 (1.1-1.5)), and non-remission off medication (OR 1.4 (1.1-1.7) 8 years after disease onset. Conclusion School absence at baseline predicted adverse long-term outcome. In children and adolescents with JIA participation in school activities is mostly high after 8 years of disease. For the minority with low participation, special attention is warranted to promote their full potential of social interaction and improve long-term outcome.